Postoperative Fistula After Different Palatoplasty Techniques - Aziz, Asif; Ullah, Hidayat (Journal of Neonatal Surgery, 2025)
Background:Postoperative oronasal fistula (ONF) is a common complication following cleft palate repair, adversely affecting speech, feeding, and overall quality of life. Various palatoplasty techniques differ in their fistula incidence and functional outcomes. Objective: To compare the incidence of postoperative fistula among three widely used palatoplasty methods—Furlow’s double opposing Z-plasty, von Langenbeck’s palatoplasty, and two-flap palatoplasty—and to identify key risk factors influencing fistula formation. Methods: A retrospective cohort study was conducted on 128 non-syndromic cleft palate patients aged 6 months to 3 years, who underwent primary palatoplasty from 2017 to 2024 at two tertiary hospitals in Khyber Pakhtunkhwa, Pakistan. Patient demographics, cleft characteristics, surgical technique, and postoperative outcomes were analyzed. Fistula incidence was assessed clinically at 1, 3 and 6-months post-surgery. Statistical analyses identified significant differences and predictors of fistula formation. Results: Fistula rates differed significantly among techniques: Furlow (2.9%), two-flap (5.3%), and von Langenbeck (14.8%) (p=0.03). The hard-soft palate junction was the most frequent fistula site. Independent risk factors included cleft width >10 mm (OR 2.6), age >18 months at surgery (OR 2.3), and von Langenbeck technique (OR 3.8). Speech and feeding problems occurred more regularly in the von Langenbeck group. Conclusion: Doing a double opposing Z-plasty helps reduce the risk of fistula after surgery stressing the importance of tension-free healing and muscle adjustment. Improvements in outcomes could be achieved by relying on sound surgical strategies with tension free closure and good and anatomical muscle approximation